2021
DOI: 10.1038/s41433-021-01621-y
|View full text |Cite
|
Sign up to set email alerts
|

Demography, clinical profile and surgical outcomes of paediatric giant retinal tear related retinal detachments

Abstract: Objective To determine the demographic profile, clinical features and surgical outcomes of giant retinal tear (GRT) related retinal detachments (RD) in children. Methods In this retrospective study, medical records of children aged 14 years and below, who underwent surgery for RD at our centre in the last 5 years were reviewed. Among these, we selected medical records of children with RDs with GRT, and examined the coloured retinal drawings, ultrawidefield photographs and/or surgical videos. Results Out of 153… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In our population, the mean age at first detachment was 10.4 years in the overall cohort, comparable with reports in the literature. 9 , 10 , 23 In the data presented here, the difference in sex was still skewed toward boys (57.9%) but not as prominently as seen in the literature (70%–80%). 2 , 9 The more equal distribution is perhaps due to the exclusion of traumatic RDs from our study.…”
Section: Discussionsupporting
confidence: 46%
“…In our population, the mean age at first detachment was 10.4 years in the overall cohort, comparable with reports in the literature. 9 , 10 , 23 In the data presented here, the difference in sex was still skewed toward boys (57.9%) but not as prominently as seen in the literature (70%–80%). 2 , 9 The more equal distribution is perhaps due to the exclusion of traumatic RDs from our study.…”
Section: Discussionsupporting
confidence: 46%
“…This is comparable with the previously reported literature showing poor anatomical and functional outcomes in pediatric cases attributed to preoperative risk factors. 34,35 Ours is a retrospective case series with the inherent limitations of a lack of a standardized surgical approach and follow-up because these decisions were patientspecific and left to the discretion of the consulting surgeon. Being a tertiary care referral center, a significant proportion included GRTD .180°with advanced PVR, contributing to poorer prognosis in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable with the previously reported literature showing poor anatomical and functional outcomes in pediatric cases attributed to preoperative risk factors. 34,35…”
Section: Discussionmentioning
confidence: 99%
“…4,5 In children, GRTs are a more common cause of rhegmatogenous RDs, with one study finding that 5.6% of detachments were secondary to GRTs. 6 Patients with GRTs are predominantly male (55% to 91%) in most studies although one larger study reported a female predominance. [7][8][9][10][11] While ocular trauma has a significant male predominance and is the strongest risk factor for GRTs, the male predominance persists when traumatic GRTs are excluded.…”
Section: Prevalencementioning
confidence: 98%
“…A large, multicenter study of RDs showed that GRTs are more common in phakic eyes (2.9%) than in pseudophakic eyes (1.5%) 4,5 . In children, GRTs are a more common cause of rhegmatogenous RDs, with one study finding that 5.6% of detachments were secondary to GRTs 6 …”
Section: Prevalencementioning
confidence: 99%